2015
DOI: 10.1158/1940-6207.capr-14-0384
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein Stabilizes Cyclin D1 and Increases Cyclin D1 Nuclear Accumulation through ERK-Mediated Inactivation of GSK-3β

Abstract: The Hepatitis B virus X protein (HBx) contributes centrally to the pathogenesis of hepatocellular carcinoma (HCC). It has been suggested that the transcriptional activation of cyclin D1 by HBx is implicated in the development of HCC. However, numerous studies have shown that overexpression of cyclin D1 alone is not sufficient to drive oncogenic transformation. Herein, we investigated whether HBx can stabilize cyclin D1 and induce cyclin D1 protein nuclear accumulation, and thereby accelerate hepatocarcinogenes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…The serine/threonine kinase Akt (also termed protein kinase B or PKB) has attracted a great deal of attention because Akt plays critical roles in the regulation of many cellular functions including metabolism, growth, proliferation, survival, transcription, and protein synthesis 25 - 29 . We found that eIF3b depletion was not associated with any significant change in Akt levels; however, the level of the activated form, p-Akt, fell in parallel with the extent of eIF3b depletion, indicating that the Akt signaling pathway was involved in such depletion.…”
Section: Resultsmentioning
confidence: 99%
“…The serine/threonine kinase Akt (also termed protein kinase B or PKB) has attracted a great deal of attention because Akt plays critical roles in the regulation of many cellular functions including metabolism, growth, proliferation, survival, transcription, and protein synthesis 25 - 29 . We found that eIF3b depletion was not associated with any significant change in Akt levels; however, the level of the activated form, p-Akt, fell in parallel with the extent of eIF3b depletion, indicating that the Akt signaling pathway was involved in such depletion.…”
Section: Resultsmentioning
confidence: 99%
“…20, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34 Moreover, AKT/GSK-3B/cyclin D1 axis was the classic pathway involved in modulation of cyclin D1 in cancer cell. 35, 36 Furthermore, EZH2 and AKT could influence expression of each other indicating that they constituted a positive loop. 21, 37, 38, 39 In addition, one-fifth of all human lncRNAs identified is physically associated with EZH2.…”
Section: Discussionmentioning
confidence: 99%
“…CYCLIN D1 regulates the G1/S phase transition during cell cycle (Resnitzky et al 1994) and can promote hepatocyte proliferation in the absence of a mitogen (Albrecht and Hansen 1999). CYCLIN D1 is also frequently over-expressed in liver tumor models and can contribute to the progression of hepatitis-induced hepatocellular carcinoma (Chen et al 2015; Masaki et al 2003; Nishida et al 1994). c-MYC, which is often over-expressed in liver cancer (Jang et al 2012; Kawate et al 1999), can also inhibit termination of differentiation, and promote hepatocyte proliferation, angiogenesis and cellular transformation, all of which can contribute to tumor promotion (Meyer and Penn 2008).…”
Section: Discussionmentioning
confidence: 99%